An Empirical Study on the Venue Attributes on Customer Satisfaction of Wedding Banquets in Sri Lanka - Bandara WMAH; Gangananda AMNM (International Journal of Engineering and Management Research, 2021)
The growth of the festival and event tourism sector has been spectacular in recent years and therefore event management has become increasingly popular with it growing and expanding equally as much as event tourism. As a most competitive industry in Sri Lanka, wedding banquet demand has a considerable increment since last few years. Recently, modern couples tend to achieve their most special occasion with a higher effort and they have been deflected for banqueting industry for having a memorable experience. Hence, the objectives of this study are to identify the existing level of venue attributes in banquet halls, to identify the relationship between those attributes and Customer satisfaction and the most influencing attributes on customer’s satisfaction. 100 of couples were selected as the sample of this study and convenience sampling method was used for selecting the sample. Data collection was done by structured questionnaires. Descriptive analysis, Pearson Correlation Coefficient and Multiple linear regressions were used for the data analysis. The findings reflect all the respondents were agreeing with existing level of attributes and all the attributes were significantly important for customer satisfaction. Decoration was the mostly influencing attribute on Customer satisfaction. Furthermore, the researcher has identified that all the independent variables showed a positive relationship with the dependent variable. Therefore, management of hotel might be considered about the enhancement of those attributes for satisfying the customers which affects the hotel demand indirectly.